An original look into pulsating heat pipes: Inverse heat conduction approach for assessing the thermal behaviour. (May 2019) - Cattani, Luca; Mangini, Daniele; Bozzoli, Fabio; Pietrasanta, Luca; Miche', Nicolas; Mameli, Mauro; Filippeschi, Sauro; Rainieri, Sara; Marengo, Marco
Highlights: A novel approach to investigate the local heat flux in PHPs is presented and tested. A infrared camera acquired the temperature maps on the external wall of the PHP. Infrared imaging is performed on a single loop PHP designed with sapphire inserts. The values of the heat exchanged between the fluid and the wall are estimated. The results are a breakthrough for developing and validating CFD simulations of PHP. Abstract: A promising solution in the field of passive two-phase heat transfer devices is represented by Pulsating Heat Pipes (PHPs). These relatively new devices, which achieve resounding interest in terms of high heat transfer capability, efficient thermal control, adaptability and low cost, have been extensively studied in the last years by many researchers. Many authors have investigated the heat fluxes at the evaporator and the condenser area only in terms of the mean values. In this work a novel approach to investigate the local heat flux in PHPs is presented and tested: the temperature distributions on the external wall of the PHP acquired with a high-speed and high-resolution infrared camera were used as input data for the inverse heat conduction problem in the wall under a solution approach based on the Tikhonov regularization method. Infrared imaging is performed on a single loop PHP designed with sapphire inserts partially coated with a highly emissive paint, allowing to determine at the same time the external wall temperature and the fluid temperature. Results show that the technique is able to show when heat is transfer from the fluid to the sapphire wall, when the hot fluid is pushed from the evaporator towards the condenser; increasing the wall tube temperature. On the contrary, when a cold fluid flows back from the condenser, the tube releases the heat previously accumulated, thereby decreasing its temperature. This approach allows to analyze the thermal behavior of the device by investigating the direct interconnection between the thermo-fluid dynamic phenomena within the PHP and the local heat flux measurements. The results proposed in this work are a breakthrough for the improvement and validation of both VOF-based DNS simulations, for local physical phenomena, and 1D simulations of the global PHP behaviour.